The problem of „billeting” of dwellings in the legislation and science of the Polish People’s Republic - Fermus-Bobowiec, Anna (Management and Administration Journal, 2023)
The article illustrates the tenancy of the dwelling units in the Polish People’s Republic. It is based on the administrative forms of housing distribution which are leading to the fact that the allocation issued by housing department (so called “billet allocation”) simultaneously formed the legal title to occupy the dwelling unit and the source of tenancy relationship. The importance of this issue arises from the fact that “billeting” was the main and most common way to meet the housing needs of the Polish People’s Republic by responding at the same time to the contemporary residential policy. The effects of “billeting” still affect tenancy and ownership issues after 1989, which often requires a recourse to the legal regulations from the period of the Polish People’s Republic. The normative material for this area of law is extensive and varied, which has been presented in the article, with simultaneous manifestation of the nature of the legal regulations, their evolution and the adopted substantive solutions. Given this range of legislation and the significance of the issue and its relevance to the reality of the Polish People’s Republic, we also have a considerable doctrine’s acquis in this topic, which has also been included in the article. These publications did not only interpret the contemporary legal regulations for the purposes of practice but were also determining the direction of legislative changes, formulating de lege ferenda postulates and providing the necessary evolution in the field of legislation.